An Overview of the Practitioner Research and Collaboration Initiative (PRACI): a practice-based research network for complementary medicine. Issue 1 (December 2017) - Steel, Amie; Sibbritt, David; Schloss, Janet; Wardle, Jon; Leach, Matthew; Diezel, Helene; Adams, Jon
Abstract Background The Practitioner Research and Collaboration Initiative (PRACI) is an innovative, multi-modality practice-based research network (PBRN) that represents fourteen complementary medicine (CM) professions across Australia. It is the largest known PBRN for complementary healthcare in the world and was launched in 2015. The purpose of this paper is to provide an update on the progress of the PRACI project, including a description of the characteristics of PRACI members in order to facilitate further sub-studies through the PRACI PBRN. Methods A CM workforce survey was distributed electronically to CM practitioners across fourteen disciplines, throughout Australia. Practitioners electing to become a member of PRACI were registered on the PBRN database. The database was interrogated and the data analysed to described sociodemographic characteristics, practice characteristics, professional qualification and practice interest of PRACI members. Results Foundational members of PRACI were found to be predominately female (76.2%) and middle-aged (82.5%). Members were primarily located in urban settings (82.5%) across the Eastern seaboard of Australia (82.5%), with few working remotely. The main modalities represented include massage therapists (58.5%), naturopaths (26.4%) and nutritionists (14.4%). The primary area of clinical interest for PRACI members were general health and well-being (75.4%), musculoskeletal complaints (72%) and pain management (62.6%). Conclusions PRACI provides an important infrastructure for complementary healthcare research in Australia and its success relies on CM practitioners being involved in the research being conducted through the PBRN. The aim of this database is to ensure that the research conducted through PRACI is rigorous, robust, clinically relevant and reflects the diversity of clinical practice amongst CM practitioners in Australia.